Hyperhomocysteinemia in Greyhounds and its Association with Hypofolatemia and Other Clinicopathologic Variables. (19th November 2016) - Heilmann, R.M.; Grützner, N.; Iazbik, M. C.; Lopes, R.; Bridges, C.S.; Suchodolski, J.S.; Couto, C. G.; Steiner, J.M.
Abstract : Background: Folate and cobalamin are essential cofactors for homocysteine (HCY) metabolism. Hyperhomocysteinemia, a multifactorial condition, may reflect B vitamin deficiency and is associated with increased risk of cardiovascular disease, thrombosis, and neurodegenerative and chronic gastrointestinal diseases in humans. Hyperhomocysteinemia has been reported in Greyhounds with suspected chronic enteropathy. Objectives: To evaluate the frequencies of and the association between hypofolatemia and hyperhomocysteinemia in Greyhounds. Animals: Data and serum samples from 559 Greyhounds. Methods: Nested case‐control study. The frequency of hypofolatemia in Greyhounds was determined by a laboratory database search. The relationship between hyperhomocysteinemia (measured by gas chromatography‐mass spectrometry) and hypocobalaminemia and hypofolatemia was evaluated, and its frequency compared between healthy Greyhounds and Greyhounds with thrombosis or chronic diarrhea. Results: Hypofolatemia was identified in 172 of 423 (41%) Greyhounds and was more common in hypo‐ than in normocobalaminemic dogs (49% vs. 35%; P = .0064). Hyperhomocysteinemia was detected in 53 of 78 (68%) of Greyhounds, being more common in hypo‐ than in normofolatemic dogs (88% vs. 59%; P = .0175). All healthy Greyhounds, 21 of 30 (70%) of dogs with chronic diarrhea and 6 of 8 (75%) of those with thrombosis, were hyperhomocysteinemic. Serum HCY concentrations were inversely correlated with serum folate concentration (ρ = −0.28; P = .0386) and were positively associated with serum albumin concentration (ρ = 0.66; P = .0022). Conclusions and Clinical Relevance: Hyperhomocysteinemia occurs frequently in the Greyhound population. Its association with hypofolatemia suggests decreased intracellular availability of B vitamins, but the functional implications warrant further investigation. Hyperhomocysteinemia in Greyhounds potentially may serve as a spontaneous canine model to further investigate hyperhomocysteinemia in humans.